Right to Education for Human Resources Development in Recent ERA in India - A Policy Perspective: Ensuring Access to Quality Education for Sustainable Human Resource Development in India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This article discusses the importance of the right to education for human resourcedevelopment in India. The Right of Children to Free and Compulsory Education (RTE) Act, 2009 is asignificant milestone in India's education system, but the implementation has been uneven. Education iscritical for economic and social development, and investment in education, improving infrastructure,teacher training, technology in education, and focus on early childhood education are essential policyperspectives for ensuring the right to education. The government must take a multi-dimensionalapproach to ensure access to quality education for all, which can unlock the full potential of India'shuman resources and ensure sustainable economic and social development.